1991
DOI: 10.1364/ao.30.003485
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the scattering of light by human hair

Abstract: We describe a general investigation into the scattering of light by human hair. The main features of the intensity distribution produced by light scattered by an individual hair are identified. Qualitative explanations for the features are advanced in terms of the arrangement of the outer structure of the hair and its level of pigmentation. Contrast gloss values are calculated in an attempt to quantify the appearance of hair. These values are found to depend not only on the properties of hair, such as color an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…It is composed of flat cells that overlap like roof shingles ( Figure 2) and make the fiber appear as a nested set of cones. Because of their overlapped arrangement, the surfaces of the scales deviate slightly but systematically from the overall normal of the fiber's surface, tilting their surfaces toward the root end of the fiber by approximately 3 • [Bustard and Smith 1991;Robbins 1994].…”
Section: Hair Fibers and Fiber Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…It is composed of flat cells that overlap like roof shingles ( Figure 2) and make the fiber appear as a nested set of cones. Because of their overlapped arrangement, the surfaces of the scales deviate slightly but systematically from the overall normal of the fiber's surface, tilting their surfaces toward the root end of the fiber by approximately 3 • [Bustard and Smith 1991;Robbins 1994].…”
Section: Hair Fibers and Fiber Scatteringmentioning
confidence: 99%
“…Second, there is a secondary lobe that occurs on the other side of the specular direction. Bustard and Smith [1991] have observed that the first peak preserves polarization, whereas the second peak is depolarized. Both groups also observed that the secondary highlight is not present in black hair.…”
Section: Introductionmentioning
confidence: 98%
“…For a number of decades, hair fiber has been the subject of intense scientific research in dermatology and cosmetology. [1][2][3] In particular, structural characterization of hair has been of special interest because the morphological features of hair have provided important biophysical clues for early diagnosis of skin disease 4 and breast cancer, 5 cosmetic assessment, 6 and forensic examination. 7 Classically, ultrastructural observation of human hair has been widely performed by using scanning electron microscopy (SEM) and transmission electron microscopy (TEM).…”
mentioning
confidence: 99%
“…54,55 Instead, human hair was primarily studied using a common confocal setup. 18,[35][36][37][38][39][40][41][42][43][44][45] A confocal setup of collimated transmittance measurement, as shown in Fig. 2, was constructed by Kharin et al 45 to examine the attenuation coefficient of human scalp hair.…”
Section: Measurement Techniquesmentioning
confidence: 99%